Can the ecological transition of cropland use narrow rural-urban income inequality? Evidence from China’s Huang-Huai-Hai Region - Linpeng Yang; Yansui Liu; Cong Ou; Yurui Li (Land Use Policy, 2026)

Advances in halide ion-mediated advanced oxidation processes for high-salinity wastewater treatment: Mechanisms of reactive oxidative species transformation and halogenated by-product formation - Yu Wang; Bing Yang; Yumin Zhang; Lingli Li; Chao Zhu; Yurui Li; Shaoqing Chen; Lili Ma; Mingyan Chen; Yucheng Liu (Chemical Engineering Journal, 2026)

Comparative genomics of parasitic and symbiotic microeukaryotes: Phylogenomic insights into lifestyle transitions and co-evolutionary dynamics - Yuexin Wang; Yihan Liu; Xiang Wang; Yurui Wang; Tengteng Zhang; Chen Shao (Molecular Phylogenetics and Evolution, 2026)

Understanding the influence of inoculum pre-conditioning on microbial community dynamics during biochemical methane potential tests - Meicai Xu; Sibel Uludag-Demirer; Sophia Liu; Yurui Zheng; Yan Liu; April Leytem; Wei Liao (Biomass and Bioenergy, 2026)

A sustainable multifunctional packaging film incorporating L-glutamic acid and curcumin: Alleviating damage and enhancing fresh produce preservation - Liping Qiao; Mengyao Zhang; Junfu Liu; Junxi Li; Yuhan Liu; Yurui Wang; Laifeng Lu; Xia Liu (Food Bioscience, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Integrating aquatic crops into rotation systems enhances soil health and suppresses potential fungal pathogens in greenhouse cucumber production - Jun Xu; Zhuoya Zhao; Liu Pan; Yuan Yao; Zhi Li; Yurui Wang; Yanfeng Li; Xuehao Chen (Applied Soil Ecology, 2026)

Multispectral analysis and molecular simulation of interaction mechanism between charged polysaccharides and myofibrillar protein in grass carp: Conformational dynamics and functional synergies - Jian Shi; Naiyong Xiao; Mingyu Yin; Jianrong Ma; Zhihui Liu; Yurui Zhang; Jianan Sun; Wenzheng Shi (Food Research International, 2026)

Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

VVFGO: a robust IMU/AHRS/USBL integrated navigation framework with adaptive virtual velocity factor correction for deep-sea docking - Ruiheng Liu; Xinyu Fei; Suohang Zhang; Yurui Zhang; Shipang Qian; Lu Wang; Yanhu Chen; Canjun Yang (Ocean Engineering, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Revealing the lifecycle evolution of hail-producing deep convective clouds by synergy of multi-source data - Qiang Li; Hongrong Shi; Yurui Xie; Rubin Jiang; Chaoying Wang; Yupeng Teng; Shuo Jia; Jianwei Wen; Disong Fu; Jiefan Yang; Xuehua Fan; Jinqiang Zhang; et al. (Atmospheric Research, 2026)

Isolation of reassortant H5N1 and H5N8 avian influenza viruses from co-infections and their host-dependent replication dynamics - Yuwei Wu; Nuo Xu; Zhifan Li; Zijun Lu; Yurui Dong; Yijie Guo; Ying Bian; Kunlin Li; Chenzhi Huo; Tao Qin; Sujuan Chen; Hui Yang; et al. (Veterinary Microbiology, 2026)

Synergistic optimization of water-energy-environment nexus under uncertainty: An interval type-2 fuzzy chance-constrained programming model in a coastal mountainous basin, China - Zhiyi Peng; Lei Jin; Yurui Fan; Li Wang; Jing Liu (Journal of Environmental Management, 2026)

Mechanistic insight into impacts of Cl− and Br− at high contents on phenol degradation and halogenated by-product formation in O3/H2O2 process - Bing Yang; Shijie Zhou; Xiangfu Huang; Qiang Zhou; Qinchuan Xu; Ying Qiu; Yurui Li; Mengnuo Wang; Yu Wang; Yuming Zhang; Mingyan Chen; Lili Ma; et al. (Process Safety and Environmental Protection, 2026)

New strategies for synergistic inhibition of mild steel corrosion by dual-functionalized chitosan: Film formation and Fe2+ adsorption - Minghui Jiang; Xiao Liu; Yurui Xu; Shiyu Li; Xingxin Hu; Xinxin Li; Lei Lu; Ziming Wang; Suping Cui (Journal of Cleaner Production, 2026)

Environmental DNA metabarcoding reveals taxon-specific community divergence between remote atolls and isolated reefs in the South China Sea - Yu Meng; Yurui Yang; Jinping Luo; Jie Yu; Ruiyu Tao; Zhihao Wang; Jiehong Liu; Wentong Xia; Fei Cheng; Songguang Xie; Yiqing Song (Acta Oceanologica Sinica, 2026)

Novel eco-friendly inhibitor for mild steel in simulated concrete pore solution: Experimental and theoretical analysis - Minghui Jiang; Xiao Liu; Xingxin Hu; Shiyu Li; Yurui Xu; Xinxin Li; Lei Lu; Chunlei Xia; Xiangju Liu; Ziming Wang; Suping Cui (Chemical Engineering Journal, 2025)

Root trait responses of Ligustrum lucidum to edaphic stress across limestone and sandy shale areas - Yurui Cheng; Yongjun Jiang; Mengni Li; Jiabin Li; Fang Liu; Peiling Zhang; Qiufang He (Plant and Soil, 2025)

Bottom-up hierarchical detection of territorial spatial pattern based on multi-source heterogeneous data - Fangxin Chen; Yurui Li; Yansui Liu (Land Use Policy, 2025)

Effects of extreme heat on vegetation carbon sequestration in the Yellow River Basin - Guanpeng Dong; Yuchen Guo; Hongjuan Zhang; Yansui Liu; Yurui Li; Han Zhang; Junting Zhong (Science China Earth Sciences, 2025)

Temperature shapes the global distribution of organic carbon in lake surface sediments - Yongquan Lin; Sheng Yang; Mengting Zhao; Xuerui Lyu; Lingmei Xu; Wengang Kang; Xinwei Yan; Yurui Zhang; Jianbao Liu (Journal of Geographical Sciences, 2025)

Impact assessment and driving mechanisms of grading and weight distribution methods on spatial zoning - Fangxin Chen; Yurui Li; Yansui Liu (Applied Geography, 2025)

Genotoxicity mode of action exploration of polyethylene glycol terephthalate (PET) acetic acid migration solution under repeated-dose exposure in rats - Liang Wang; Li Cao; Xiaoya Wang; Yufei Liu; Weiwei Zhang; Yurui Gou; Jun He; Jiao Huo; Xiaomeng Li; Jinyao Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

Government subsidy strategies for new energy vehicle charging infrastructure considering consumers’ low-carbon preference: A tripartite evolutionary game model - Songsong Liu; Tingting Li; Yurui Chen; Chang Lyu; Fengyong Zhai (Energy Policy, 2025)

Spatial-temporal evolution and coupling coordination of land use functions across China by fusing multiple-source heterogeneous data - Fangxin Chen; Yurui Li; Yansui Liu (Land Use Policy, 2025)

Significantly enhanced piezoelectric properties of BaTiO3-based ceramics with unchanged curie temperature via local chemical inhomogeneity - Ming Wu; Ruifeng Yao; Chengyichang Jin; Yurui Xu; Jingzhe Xu; Liqiang He; Yang Yang; Yongbin Liu; Lisheng Zhong; Jinghui Gao (Chemical Engineering Journal, 2025)

Design of the TP-1B satellite’s laser retro-reflector array and analysis of laser ranging - Qingshan Luo; Xu Liu; Tao Yang; Yurui Xu; Wei Zhu; Yunsheng Yao (Advances in Space Research, 2025)

Improved semi-infinite interval type-2 fuzzy multi-objective programming with integrated multi-criteria decision analysis for sustainable water resource management - Xi Zhang; Lei Jin; Yurui Fan; Li Wang; Jing Liu; Pangpang Gao (Journal of Water Process Engineering, 2025)

Poleward expansion of North Pacific gyre circulation during the warm early Eocene inferred from inter-model comparisons - Yurui Zhang; Agatha M. de Boer; Guojin Qin; Daniel J. Lunt; David K. Hutchinson; Sebastian Steinig; Igor Niezgodzki; Bridget S. Wade; Xiaoqing Liu; Christopher J. Poulsen; Gerrit Lohmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Distribution and ecological risks of microplastics in a tropical tourism island area in Hainan, China - Weijie Bian; Rui Sun; Yurui Li; Shuguo Lü; Dongwei Yang; Hongbo Li; Yingxu Zeng; Min Liu (Journal of Oceanology and Limnology, 2025)

Unveiling the neglected impacts of halide ions on phenol removal in UV/H2O2 system: Light shielding and oxidant utilization efficiency - Bing Yang; Ying Qiu; Qiuping Luo; Xiangfu Huang; Yurui Li; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Water Process Engineering, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Microplastic pollution in tropical coral reef ecosystems from the coastal South China Sea and their impacts on corals in situ - Weijie Bian; Yingxu Zeng; Yurui Li; Guangshui Na; Jun Mu; Shuguo Lv; Min Liu (Journal of Hazardous Materials, 2024)

Investigation on the rotary atomization evaporation of high-salinity desulfurization wastewater: Performance and products insights - Yurui Wang; Lingxiao Zhan; Qiwei Luo; Heng Chen; Juecen Mao; Jun Wan; Chaozhen Liu; Haijie Chen; Suoqi Zheng; Zhanxing Chen; Zhihao Li; Linjun Yang (Journal of Environmental Management, 2024)

Advances in modified zero-valent iron materials: Synthesis methods, field studies, practical applications and challenges - Yurui Li; Shijie Zhou; Yuan Meng; Ying Qiu; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu; Bing Yang (Chemical Engineering Journal, 2024)

Unveiling the kinetics and mechanism of sulfide-modified zero-valent iron activated hydrogen peroxide for phenol degradation - Bing Yang; Yurui Li; Yuan Meng; Ying Qiu; Mi Zhou; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Environmental Chemical Engineering, 2024)

Feasibility and application of soil reconstruction technology for farmland consolidation in China's Loess Plateau - Weilun Feng; Yansui Liu; Yurui Li (Land Use Policy, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Orbital modulation of an intensified hydrological cycle during the Paleocene-Eocene Thermal Maximum - Jingyu Zhang; Chunlian Wang; Xiaohua Teng; David B. Kemp; Zhixiang Wang; Hu Yang; Congcong Gai; Yurui Zhang; Yi Zhong; Xiaodong Jiang; Qi Zhang; Weijie Zhang; et al. (Earth and Planetary Science Letters, 2024)

TIC-driven sustainable land use mode in the Loess Plateau: A case study of gully land consolidation project in Yan'an City, China - Yanjun Guo; Yansui Liu; Ruotong Li; Yurui Li; Jieyong Wang (Land Use Policy, 2024)

Freezing pre-treatment improves radio frequency explosion puffing (RFEP) quality by altering the cellular structure of purple sweet potato [Ipomoea batatas (L) Lam.] - Chao Mao; Yurui Chen; Tong Liu; Pengfei Ye; Yequn Wang; Xiangwei Chen; Hongfei Fu; Yunyang Wang; Ke Wang (Food Research International, 2024)

Effects of exogenous steroid hormones on growth, body color, and gonadal development in the Opsariichthys bidens - Qingyuan Liu; Jinchun Hu; Yurui Lin; Xinrui Wu; Yujun Feng; Jiazheng Ye; Kai Zhang; Shanjian Zheng (Fish Physiology and Biochemistry, 2024)

Hypoxia Potentiated Lung Cancer Cell Migration and Invasion by up-regulating HIF1α/JAK2/STAT3 Axis and Activating MMP13 Transcription - Xiaoju Cheng; Damin Liang; Xiaoqian Li; Chengmin Deng; Meng Ye; Jiao Yang; Yurui Liu; Kaifeng Wu; Jie Wu; Peng Tian (Cell Biochemistry and Biophysics, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Environmental responsibility, emotion and public water-saving behavior - Xingle Long; Yurui Liu; Wensi Cheng; Jinyu Zhang; Chuanmin Jin; Si’an Tao (Environment, Development and Sustainability, 2023)

Rutin hydrate relieves neuroinflammation in zebrafish models: Involvement of NF-κB pathway as a central network - Ying Hu; Kun Jia; Yatong Zhou; Lixin Chen; Fei Wang; Xiaokun Yi; Yong Huang; Yurui Ge; Xiaomei Chen; Dalong Liao; Yuyang Peng; Yunlong Meng; et al. (Fish & Shellfish Immunology, 2023)

Regularity of rural settlement changes driven by rapid urbanization in North China over the three decades - Yansui Liu; Cong Ou; Yurui Li; Liqiang Zhang; Jianhua He (Science Bulletin, 2023)

Distinguishing anaerobic digestion from electrochemical anaerobic digestion: Metabolic pathways and the role of the microbial community - Nan Wang; Yutong Yang; Kunde Xu; Xiangang Long; Yurui Zhang; Hongzhou Liu; Tiezhu Chen; Jianchang Li (Chemosphere, 2023)

Feasibility analysis of a double-cropping system for the efficient use of farmland on China’s Loess Plateau - Weilun Feng; Yansui Liu; Yurui Li; Zongfeng Chen (Journal of Geographical Sciences, 2023)

Optimizing field management to promote the ecologicalization of agriculture in loess hilly-gully region, China - Yunxin Huang; Yurui Li; Yansui Liu (Journal of Geographical Sciences, 2023)

An algal-bacterial symbiotic system of carbon fixation using formate as a carbon source - Yurui Zheng; Jeffrey J. Czajka; Carly Daiek; Zhichang Yang; Liangliang Sun; Yinjie J. Tang; Yan Liu; Wei Liao (Algal Research, 2023)

Design and testing of a mechanized brush-screen cooperative vibration harvester for mudflat-buried shellfish based on the discrete element method - Hangqi Li; Gang Mu; Hanbing Zhang; Hao Wu; Fawei Liu; Zhenyin Sun; Qian Zhang; Yizhou Wang; Yurui Wang; Xiuchen Li; Guochen Zhang (Frontiers in Marine Science, 2023)
Introduction To enhance the application of mechanized harvesting and supplement research on harvesting theory in mudflat-buried shellfish harvesting in China, a brush-screen cooperative mudflat-buried shellfish vibration harvester was designed. Methods The harvester is primarily composed of a crank rocker double-layer vibrating screen, two stage rolling brush, and a conveyor chain. White clams ( Mactra veneriformis ) cultured in mudflats were used as the research objects in this paper, and the mechanics and motion states of the shellfish on the vibrating screen were analyzed. The shellfish harvesting simulation response surface experiments based on the discrete element method (DEM) were conducted to analyze the influence of the main operating parameters on the quantity of shellfish harvested. Results The results revealed that the number of shellfish harvested was significantly influenced ( p < 0.01) by vibrating screen amplitude, first-stage spiral rolling stainless steel brush rotation rate, and harvester travel speed. The optimal combination of key parameters was 1.4 mm, 40 rpm, and 10 m/min, respectively. With these values, the projected shellfish crushing rate was 2.82% and the shellfish harvesting efficiency was 125 pieces/m 2 . The equipment was then manufactured and the shellfish harvesting verification test was performed under the same operating parameters as the simulation. Test results indicated that the harvesting efficiency of the equipment was 114 pieces/m 2 and the shellfish crushing rate was 6.97%. Discussion The shellfish harvesting work could be completed by the equipment effectively and with low loss. The results of this study provide a theoretical reference for a novel mechanized method of harvesting mudflat-buried shellfish.

Development of chemical admixtures for green and environmentally friendly concrete: A review - Guanghong Lai; Xiao Liu; Shiyu Li; Yurui Xu; Yunsheng Zheng; Jianan Guan; Ruijun Gao; Zhongyuan Wei; Ziming Wang; Suping Cui (Journal of Cleaner Production, 2023)

Scenario analysis of high and steep cutting slopes protection in the loess hilly region: A case study of the Yangjuangou catchment in Yan’an, China - Zhi Cao; Yurui Li; Yansui Liu; Yanxia Lu (CATENA, 2023)

Projections of future precipitation and air temperature over the Tibetan Plateau based on Coupled Model Intercomparison Project Phase 6 multimodel ensembles - Wenqing Zhang; Liu Liu; Yurui Lun; Lei Cheng; Xiuping Li; Zongxue Xu (International Journal of Climatology, 2022)
In the context of global warming and the release of projection results from the Coupled Model Intercomparison Project Phase 6 (CMIP6), it is important to conduct research on climate change on the Tibetan Plateau (TP) which exhibits unique geographic characteristics and complex climatic conditions. Using 10 general circulation models (GCMs) from CMIP6 corrected for bias by the daily translation (DT) method, we investigated the projected changes in precipitation and air temperature for the mid‐term (2031–2050) and long‐term (2061–2080) of the 21st century on the TP after evaluating the reliability of the bias correction, for four scenarios based on different combinations of shared socioeconomic pathways and representative concentration pathways. The multimodel ensembles (MMEs) indicated that the projected annual precipitation shows an increasing trend for the mid‐term and long‐term periods, with the projected increase for the long‐term primarily concentrated in areas with less precipitation. Meanwhile, the future precipitation changes exhibit a significant elevation dependency. The rate of increase of precipitation firstly fluctuates and then gradually increases along with the elevation increasing from 1,500 to 5,800 m. The valley value of rate mainly appears in two elevation zones (2,200–2,600 m and 3,400–3,800 m). The projected temporal changes in annual air temperatures reveal obvious warming over the TP. The projected warming is overall more pronounced with increase in elevation; however, it reaches a peak at approximately 5,000–5,200 m and then slows down slightly, indicating that warming is not dependent on elevation in the higher elevation zones. The present results have important implications for investigating the impacts of climate change on the water cycle in alpine regions.

Cloning and Expression of Sox2 and Sox9 in Embryonic and Gonadal Development of Lutraria sieboldii - Min Lu; Zenghou Xing; Yurui Zhou; Youhou Xu; Huijing Peng; Jie Zou; Solomon Felix Dan; Zhicai She; Pengliang Wang; Jinfeng Liu; Shaomin Qin; Jialin Yang; et al. (Fishes, 2022)
The Sox family plays essential roles as transcription factors in vertebrates; however, little is known about the Sox family in Lutraria sieboldii. L. sieboldii are pleasant to eat with a short growth cycle and have become one of the best bottom-seeded enrichment species in Guang Xi. In this study, Sox2 (named LsSox2) and Sox9 (named LsSox9) from L. sieboldii were cloned, and their expression patterns were analyzed. The length of the LsSox2 gene coding sequence was 1011 bp, encoding 336 amino acids, and LsSox9 was 1449 bp, encoding 482 amino acids. LsSox2 had its highest expression levels in the ovary, which were 356 times those in testis, whereas LsSox9 presented higher expression in testis, which was 6 times more highly expressed than in the ovary. LsSox2 exhibited the highest expression during the morula stage, which was 20 times that of the D-shaped larvae or zygote. LsSox9 exhibited two expression peaks, one at the four-cell stage and the other at the trochophore stage, while the lowest expression was in the zygote. LsSox9 was 73 times more highly expressed in the four-cell stage than in the zygote stage. During gonadal development, LsSox2 presented the highest expression in the mature ovary, which was 756 times more highly expressed than in mature testis. LsSox9 presented higher expression in testis at the emission stage which was 6 times more highly expressed than in the ovary. These results indicate that LsSox2 and LsSox9 may play important roles in embryonic and gonadal development.

Whole Genomic DNA Methylation Profiling of CpG Sites in Promoter Regions of Dorsal Root Ganglion in Diabetic Neuropathic Pain Mice - Wen Chen; Ting Lan; Qingyu Sun; Yurui Zhang; Danmin Shen; Tingting Hu; Jing Liu; Yingzi Chong; Peipei Wang; Qian Li; Weihua Cui; Fei Yang (Journal of Molecular Neuroscience, 2021)

Assessment of GCMs simulation performance for precipitation and temperature from CMIP5 to CMIP6 over the Tibetan Plateau - Yurui Lun; Liu Liu; Lei Cheng; Xiuping Li; Hao Li; Zongxue Xu (International Journal of Climatology, 2021)
General circulation models (GCMs) are indispensable for climate change adaptive study over the Tibetan Plateau (TP), which is the potential trigger and amplifier in global climate fluctuations. With the release of Coupled Model Intercomparison Project Phase 6 (CMIP6), 24 GCMs from CMIP5 and CMIP6 were comparatively evaluated for precipitation and air temperature simulations based on the China Meteorological Forcing Dataset (CMFD). Rank score results showed that CMIP6 models generally performed better than CMIP5 for precipitation and surface air temperature over the TP. According to multimodel ensembles (MMEs) of the optimal GCMs for each climate variable, the overestimation of precipitation was both present in CMIP5 and CMIP6, but the results of CMIP6 MMEs were relatively lower in the mid‐west and northern edge of the TP. Furthermore, CMIP6 offered a better performance of precipitation in summer and autumn. For temperature, CMIP6 MMEs were able to reduce the relatively large cold bias that appeared in CMIP5 MMEs in northwest areas to about 1°C and had a smaller bias in spring and winter. Moreover, the investigation into the simulation effects of precipitation at different elevation zones demonstrated that the improved ability of CMIP6 MMEs to reduce bias was mainly concentrated in the elevation zones of 2,000–3,000 m and over 5,000 m, where the precipitation bias was more than 200%. Additionally, CMIP6 MMEs of temperature were able to reduce the bias to less than 2°C in each elevation zone, with the minimum bias of −0.22°C distributed in the region with altitudes from 3,000 to 4,000 m, while the biases of CMIP5 MMEs in the region of 4,000–5,000 m and over 5,000 m were smaller than those of CMIP6 MMEs. Findings obtained in this study could provide a scientific reference for related climate change research over the TP. GCMs of CMIP6 perform better than those of CMIP5 for precipitation and temperature over the TP. Multimodel ensembles (MMEs) of CMIP6 effectively reduce the overestimation of precipitation from CMIP5 MMEs by 40 mm at the annual scale. Improved ability of CMIP6 MMEs shows a significant elevation dependency, especially in elevation zones of 2,000–3,000 m and over 5,000 m for precipitation.

Effect of Maize Straw Biochar on Bacterial Communities in Agricultural Soil - Jie Liu; Yanli Ding; Yurui Ji; Guanghai Gao; Yingying Wang (Bulletin of Environmental Contamination and Toxicology, 2020)

Quantifying the vertical distribution pattern of land-use conversion in the loess hilly region of northern Shaanxi Province 1995–2015 - Zhi Cao; Yurui Li; Zhengjia Liu; Lingfan Yang (Journal of Geographical Sciences, 2019)

Land use and landscape change driven by gully land consolidation project: A case study of a typical watershed in the Loess Plateau - Yurui Li; Yi Li; Pengcan Fan; Jian Sun; Yansui Liu (Journal of Geographical Sciences, 2019)

Extended warm temperate zone and opportunities for cropping system change in the Loess Plateau of China - Zhengjia Liu; Yansui Liu; Yurui Li (International Journal of Climatology, 2019)
Thermal condition changes largely affect crop phenology, cropping systems and crop field. In this study, we used long‐term (1961–2015) annual accumulated temperature ≥10 °C (AAT10) derived from daily gridded air temperature to investigate the potential implication of AAT10 changes for regional agriculture development in the Loess Plateau (LP). Results showed that an elevation‐dependent spatial pattern of AAT10 was observed. Southeastern LP with low elevation had higher AAT10 and western LP with high elevation had lower AAT10. Across the LP, the start date of 5‐day moving average temperature () ≥10 °C (SDT10) showed significantly advanced trends ( p p R 2 = 0.76, p R 2 = 0.64, p

Histone methyltransferase TXR1 is required for both H3 and H3.3 lysine 27 methylation in the well-known ciliated protist Tetrahymena thermophila - Xiaolu Zhao; Yuanyuan Wang; Yurui Wang; Yifan Liu; Shan Gao (Science China Life Sciences, 2017)

Enzymatic and chemical mapping of nucleosome distribution in purified micro- and macronuclei of the ciliated model organism, Tetrahymena thermophila - Xiao Chen; Shan Gao; Yifan Liu; Yuanyuan Wang; Yurui Wang; Weibo Song (Science China Life Sciences, 2016)

Progress of research on urban-rural transformation and rural development in China in the past decade and future prospects - Yansui Liu; Hualou Long; Yufu Chen; Jieyong Wang; Yurui Li; Yuheng Li; Yuanyuan Yang; Yang Zhou (Journal of Geographical Sciences, 2016)

Differentiation regularity of urban-rural equalized development at prefecture-level city in China - Yansui Liu; Cong Schen; Yurui Li (Journal of Geographical Sciences, 2015)

GIS-based effect assessment of soil erosion before and after gully land consolidation: A case study of Wangjiagou project region, Loess Plateau - Yansui Liu; Yanjun Guo; Yurui Li; Yuheng Li (Chinese Geographical Science, 2015)

Characteristics of porosity and permeability layer of fossil Halimeda reef mineral rock of Miocene in the Xisha Islands and its genetic model - Hong Xu; Yurui Zhu; G. P. Eberli; Wei Luo; Xinwei Zhao; Ying Cai; Xinyu Liu; Guijing Yan; Bolin Zhang; Kai Wei; Ruyong Cui (Acta Oceanologica Sinica, 2015)

Biogenic carbonate formation and sedimentation in the Xisha Islands: evidences from living Halimeda - Hong Xu; Xinwei Zhao; G. P. Eberli; Xinyu Liu; Yurui Zhu; Ying Cai; Wei Luo; Guijing Yan; Bolin Zhang; Kai Wei; Jian Shi (Acta Oceanologica Sinica, 2015)

Dynamic trends and driving forces of land use intensification of cultivated land in China - Guogang Wang; Yansui Liu; Yurui Li; Yangfen Chen (Journal of Geographical Sciences, 2015)

Problem regions and regional problems of socioeconomic development in China: A perspective from the coordinated development of industrialization, informatization, urbanization and agricultural modernization - Yurui Li; Jing Wang; Yansui Liu; Hualou Long (Journal of Geographical Sciences, 2014)

Bioherm petroleum reservoir types and features in main sedimentary basins of the South China Sea - Hong Xu; Jing Sun; Jing Liao; Gang Dong; Jinqing Liu; Hongying Song; Zhenfeng Wang; Zhipeng Sun; Qinghuan Jin; Li Zhang; Kai Wei; Yurui Zhu; et al. (Journal of Earth Science, 2012)

Inexact fuzzy two-stage programming for water resources management in an environment of fuzziness and randomness - Qing Hu; Guohe Huang; Zhenfang Liu; Yurui Fan; Wei Li (Stochastic Environmental Research and Risk Assessment, 2012)